1997
DOI: 10.1080/01411599708228790
|View full text |Cite
|
Sign up to set email alerts
|

New experimental developments in Raman spectroscopy at high pressures and temperatures on crystalline and amorphous phases

Abstract: Recent developments in Raman spectroscopy at high pressure, high temperature and combined high pressure and variable temperature are presented. The instrumental and technical aspects of Raman spectroscopy, and coupling 'of diamond anvil cells and miniature furnaces to Raman microspectrometers are discussed. Several pitfalls are discussed: (1) the generation of shear stresses on the sample during room temperature compression and their effects on phase transitions; (2) thermal radiation during hightemperature me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…However, we cannot exclude that the bands' broadness, in addition to poorly resolved components, can also be due to a partial amorphization of the sample. This amorphization phenomenon has been observed on other perovskites (19). After the pressure release, spectra are similar to the initial ones for all compositions, which indicates the reversibility of the transitions.…”
Section: Phase Transitions Of Bacesupporting
confidence: 49%
“…However, we cannot exclude that the bands' broadness, in addition to poorly resolved components, can also be due to a partial amorphization of the sample. This amorphization phenomenon has been observed on other perovskites (19). After the pressure release, spectra are similar to the initial ones for all compositions, which indicates the reversibility of the transitions.…”
Section: Phase Transitions Of Bacesupporting
confidence: 49%
“…Such high-temperature measurements have been performed using a pulsed-excitation method 1,2 and a micro-Raman technique. 3,4 However, these techniques require a quite high energy density (typically 80 -5000 kW in 5-10 ns for the pulsed-excitation method), which would cause serious damage to the sample. We have demonstrated that Raman scattering using ultraviolet (UV) excitation is well suited for in situ investigation of materials at high temperatures up to 1773 K ( Fig.…”
Section: Introductionmentioning
confidence: 99%